The Role of Housewives in Handling the Waste Problem in Pekanbaru City - Willya Achmad (Jurnal EduHealth, 2023)
Waste management in Pekanbaru City is a classic problem that has not been resolved because of the behavior or public awareness that is still lacking in environmental cleanliness. This waste generally comes from the activities of residents who litter, both organic and inorganic waste in the form of drink bottles, plastic food boxes, and other plastic materials. The purpose of this study was to determine the role of housewives in Pekanbaru City in dealing with waste problems. This study uses a quantitative approach with a cross sectional research design. The results showed that in general the role of housewives in handling waste in the village of Kampung Baru, Senapelan district, Pekanbaru City, it can be seen that most housewives behave badly in waste management, namely 47 housewives (52.8%), good knowledge of about 71 housewives (79.8%), positive attitude as many as 81 housewives (91.0%), inadequate infrastructure facilities as many as 62 housewives (69.7%), local regulations are not implemented as many as 50 housewives (56.2%).